Women, state, and revolution : essays on power and gender in Europe since 1789 - Reynolds, Sián. (Brighton, Sussex : Wheatsheaf Books, 1986)
The book makes a major contribution to our understanding of the historical role of women in European politics.
Includes index.
Includes bibliographical references: p. 172-184.
II 15/01/2019
Loans
Keywords: Women; Feminism